The influence of primary care quality on hospital admissions for people with dementia in England: a regression analysis. - Panagiotis Kasteridis; Anne R Mason; Maria K Goddard; Rowena Jacobs; Rita Santos; Gerard McGonigal (PLoS ONE)
Objectives To test the impact of a UK pay-for-performance indicator, the Quality and Outcomes Framework (QOF) dementia review, on three types of hospital admission for people with dementia: emergency admissions where dementia was the primary diagnosis; emergency admissions for ambulatory care sensitive conditions (ACSCs); and elective admissions for cataract, hip replacement, hernia, prostate disease, or hearing loss. Methods Count data regression analyses of hospital admissions from 8,304 English general practices from 2006/7 to 2010/11. We identified relevant admissions from national Hospital Episode Statistics and aggregated them to practice level. We merged these with practice-level data on the QOF dementia review. In the base case, the exposure measure was the reported QOF register. As dementia is commonly under-diagnosed, we tested a predicted practice register based on consensus estimates. We adjusted for practice characteristics including measures of deprivation and uptake of a social benefit to purchase care services (Attendance Allowance). Results In the base case analysis, higher QOF achievement had no significant effect on any type of hospital admission. However, when the predicted register was used to account for under-diagnosis, a one-percentage point improvement in QOF achievement was associated with a small reduction in emergency admissions for both dementia (-0.1%; P=0.011) and ACSCs (-0.1%; P=0.001). In areas of greater deprivation, uptake of Attendance Allowance was consistently associated with significantly lower emergency admissions. In all analyses, practices with a higher proportion of nursing home patients had significantly lower admission rates for elective and emergency care. Conclusion In one of three analyses at practice level, the QOF review for dementia was associated with a small but significant reduction in unplanned hospital admissions. Given the rising prevalence of dementia, increasing pressures on acute hospital beds and poor outcomes associated with hospital stays for this patient group, this small change may be clinically and economically relevant.